PERLINDUNGAN HUKUM TERHADAP PEKERJA/BURUH PENERIMA UPAH DALAM SUATU PERUSAHAAN YANG TIDAK DIIKUTSERTAKAN DALAM KEANGGOTAAN BPJS KETENAGAKERJAAN DITINJAU DARI UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BPJS - Ulfa Luthfiana (PROGRESIF: Jurnal Hukum, 2016)
The purpose of this study is to know the legal protection received by labors who work in a company that is not a member of Workers Social Security Agency (BPJS Ketenagakerjaan) viewed from Law Number 24 of 2011 on BPJS. This is a jurnal empirical study. The study was conducted at the office of BPJS Ketenagakerjaan Pangkalpinang, Social Services and Employment of Pangkalpinang City, KSPSI of Bangka Belitung Province. To gather the data, interviews and observation wer conducted along with library research. To analyze the data, qualitative method with interactive model was employed. The result shows that membership of BPJS Ketenagakerjaan is BPJS’ preventive step to give legal protection. Law number 24 of 2011 has firmly stipulated that sanctions will be given to employers who fail to register and pay dues for their employees. The administrative sanction takes from of written admonition, fines of IDR 1.000.000.000,00